Nilai-nilai Pendidikan Agama Islam dalam Tradisi Nyadran: Studi Perspektif Masyarakat Lokal Di Desa Jungpasir Kecamatan Wedung Kabupaten Demak - Hilmatul Bariroh; Mufid Mufid (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
This study aims to examine and analyze the values of Islamic Religious Education (PAI) contained in the Nyadran Tradition from the perspective of the local community of Jungpasir Village, Wedung District, Demak Regency. The Nyadran tradition in Jungpasir Village is unique because it explicitly functions as a substitute for the Sedekah Bumi tradition, combining the purpose of agricultural gratitude with Islamic religious rituals. This study uses a qualitative method with an ethnographic approach, allowing researchers to holistically describe cultural patterns, beliefs, and the process of internalizing religious values within the community. Data was collected through observation (of the Kirab Sesaji and Tirakatan), in-depth interviews with various key informants (religious leaders, traditional leaders, and youth), and documentation, with data validity testing using triangulation. The results of the study show that Nyadran is rich in Islamic religious education values that are lived by the local community, including the values of Aqidah (avoidance of shirk, reminders of death/the afterlife through tahlil), Ibadah and Akhlak (gratitude, generosity, almsgiving/feasting), and Kebersamaan (social solidarity and mutual cooperation). Functionally, the community interprets Nyadran not only as a ritual to honor their ancestors, but also as an authentic medium for Islamic Religious Education that is effective in strengthening character education based on Islamic values and maintaining social harmony in Jungpasir Village.